2019
DOI: 10.26809/joa.4.013
|View full text |Cite
|
Sign up to set email alerts
|

Çocuklarda Özerkli̇k Algisi İle Öğretmenleri̇n Özerkli̇ği̇ Etki̇leyen Faktörler Ve Geli̇şti̇rmeye Yöneli̇k Strateji̇lere İli̇şki̇n Görüşleri̇

Abstract: Bu araştırma, okul öncesi eğitimine devam eden altı yaş çocuklarının özerklik algılarını ve öğretmenlerin, çocuklarda özerkliği etkileyen faktörler ile özerkliği geliştirmeye yönelik stratejiler hakkındaki görüşlerini belirlemek amacıyla yapılmıştır. Araştırma, tarama modelinde betimsel bir çalışmadır. Araştırmanın çalışma grubu, 2016-2017 eğitim-öğretim yılı bahar döneminde Türkiye'nin güneyinde bulunan bir şehirdeki dört anaokulundan seçkisiz olarak belirlenen 110 çocuk ve onların öğretmenlerinden oluşmuştur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
1
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 14 publications
0
1
0
Order By: Relevance
“…In this sense, it was found that children define freedom mainly as "playing outdoors"; they use terms for freedom outside of play such as "forbidden, permission, growth, doing what they want, being able to behave freely". According to Ölçer and Yılmaz (2019), children's views on the concept of freedom were divided into three categories: Behavioral autonomy, social-emotional autonomy, and cognitive autonomy, and their approach to the concept of freedom is primarily behavioral autonomy, which is defined as individuals' control over their behavior and taking responsibility for their behavior (51.64%), and they see play as a place of freedom. It can be argued that children feel most free when playing outdoors and in the community, especially when they play together.…”
Section: Discussionmentioning
confidence: 99%
“…In this sense, it was found that children define freedom mainly as "playing outdoors"; they use terms for freedom outside of play such as "forbidden, permission, growth, doing what they want, being able to behave freely". According to Ölçer and Yılmaz (2019), children's views on the concept of freedom were divided into three categories: Behavioral autonomy, social-emotional autonomy, and cognitive autonomy, and their approach to the concept of freedom is primarily behavioral autonomy, which is defined as individuals' control over their behavior and taking responsibility for their behavior (51.64%), and they see play as a place of freedom. It can be argued that children feel most free when playing outdoors and in the community, especially when they play together.…”
Section: Discussionmentioning
confidence: 99%
“…Yavuz (2016) writes that student autonomy also means that the student is the subject in the decisions made in their learning process. According to Ölçer and Yılmaz (2019), autonomy is the ability to be aware of one's self, to think freely and decide, to put one's decisions into action, to act independently and sincerely, and to make choices. Individuals' behaviors such as feeling confident about their choices, resisting peer and parent pressure while displaying appropriate social responsibility, having control over their behaviors, feeling self-confident, and being able to make decisions without getting socially affected depend on the development of autonomous behaviors (Yılmaz and Ölçer, 2018).…”
Section: Discussionmentioning
confidence: 99%